Evolutionarily-conserved MZIP2 is essential for crossover formation in mammalian meiosis - Zhang, Qianting (Commun Biol, 2018)
During meiosis, formation of crossovers—the physical links that ensure the segregation of homologous chromosomes—requires a group of evolutionarily conserved ZMM proteins. In budding yeast, three ZMM proteins, Zip2, Spo16, and Zip4, form a trimeric complex to bind recombination intermediates and promote crossover formation. Here, we show that MZIP2 is the mammalian ortholog of Zip2. Complete ablation of MZIP2 in mice caused sterility in both males and females, as well as defects in repairing meiotic DNA double-strand breaks. MZIP2 forms discrete foci on chromosomes axes, and is required for the localization of TEX11 (mammalian Zip4 ortholog) and another ZMM protein, MSH4, to form crossover-prone recombination intermediates. As a consequence, formation of crossovers is abolished and formation of synaptonemal complex is incomplete in MZIP2-null meiocytes, resulting in meiosis arrest at a zygotene-like stage. Our results suggest that the processing of early recombination intermediates toward mature crossovers is dependent on MZIP2.